Theatre, Parody and Politics in Wilkie Collins's No Name - Jones, Miriam (2022)
This thesis uncovers a systematic theatrical subtext in Wilkie Collins’s 1862-3 novel No Name. It aims to demonstrate that No Name is created from parodies of plays in imagined performance, including aspects of their live performance and production such as sets and costumes, as well as their characters and plots. Focussing on the detailed parody within No Name of the whole of four important dramatic works, the thesis argues that recognition of these parodies suggests new interpretations of this novel and reveals Collins to be a far more sophisticated and ambitious writer than previously supposed. The operation of the parodies within the text seem to articulate critiques and opinions about the fiction, theatre and politics of Collins’s world. His use of intertextuality, theatricality and parody highlight the artificiality of fiction, suggesting dissent from the cultural preference for realism. The analogies created between the content of dramas and that of the novel suggest social and political comment, especially on contemporary inequalities, such as the dominance of a privileged male elite and the disadvantaged position of women. Both aspects seem to explore the construction of social norms and the links between the cultural value for certain types of art and the maintenance of the prevailing political and social hierarchy. The subtext also reveals Collins’s deep engagement with and knowledge of theatre, its practice and its history. The importance of theatre to Collins as a writer has also gone largely unrecognised.